An in vitro-in vivo correlation study of modified release formulations of Venlafaxine.HCl - Aravindaraj, J.R; Manikandan, D.; Nanjan, Moola Joghee (São Paulo State University (UNESP), 2014)
A single dose, randomized, complete and four treatment cross over study was conducted in healthy human subjects for IVIVC of venlafaxine.HCl, Plasma concentrations were estimated by a simple, rapid, sensitive and validated LCMS method, Cetirizine was used as the internal standard (IS), The analytes and the IS were extracted from the human plasma by liquid-liquid extraction technique, The reconstituted samples were chromatographed on Kromasil C18 column using an isocratic solvent mixture [acetonitrile-water, 90:10 (v/v)] at a flow rate of 0.5 mL/min, Method validation was performed as per FDA guidelines and the results met the acceptance criteria, USP dissolution apparatus I (Basket) and pH 6.8 at 100 rpm was found to yield acceptable IVIVC for the drug, The developed dissolution method would discriminate bioinequivalent batches, A 'Level A' correlation was observed for the selected formulations at the in vitro dissolution conditions developed, The dissolution method predicted the best absorption rate for the selected modified release formulations, The validity of the correlation was assessed by determining how well the IVIVC model could predict the rate and the extent of absorption as characterized by Cmax and AUC, A percent prediction error of = 10 % for C max and AUC obtained establishes the predictability of the developed IVIVC model, It may, therefore, be concluded that the developed dissolution method can surrogate for human bioequivalence study.